Webite-Based Student Enrollment System at MTs Al Anwar Perak Jombang - Asadullah, Ahmad Insani; Munawarah, Munawarah (NEWTON: Networking and Information Technology, 2024)
Each year, MTs Al Anwar faces two lessons learned from managing the student admission process (PPDB). This manual process traditionally applied raises many problems like Time (Inefficiency in times management), Errors and Difficulties to follow up enrollments. This research focuses on the development of a web-based student admission information system to solve these problems. The research method that authors apply is the system development method with Waterfall model such as analysis, design, implementation testing maintenance. The System Developed with PHP and MySQL system has been developed by the programming language. The system offers a number of features such as registration, vetting and data collection (student information), monitoring & evaluation. In this study, the sample is some of the registration staff at MTs Al Anwar in Jombang City and also parents who are enrolling their children. The findings of this study showed a new implementation web-based PPDB Information System that is increasing efficiency and the accuracy on New Student Admission Process at MTs Al Anwar. After being currently used by users (PPDB committee and prospective students/parents), the response they gave was good because of its user friendly features as well transparency provided. This system is a great addition not only providing positive values for both prospective students and their family members or legal guardians, but also it improves KTSP at MTs Al Anwar.